ALJM-based Efficient VLSI Architecture for Fast-ICA in Real-time Signal - SAJJAD, MUHAMMAD (2021)
Independent component analysis (ICA) is one of the statistical techniques to solve the problem of blind source separation (BSS). Fast ICA (FastICA) is the most widely used algorithm for ICA.